1998
DOI: 10.1126/science.280.5369.1550
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Glasses and Glass-Forming Liquids Studied by Inelastic X-ray Scattering

Abstract: The development of inelastic x-ray scattering with millielectron volt energy resolution at the European Synchrotron Radiation Facility in Grenoble, France, provides a method for studying high-frequency collective dynamics in disordered systems. This has led to the observation of propagating acoustic phonon-like excitations in glasses and glass-forming liquids down to wavelengths comparable to the interparticle distance. Using the inelastic x-ray scattering results on glycerol as a representative example, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
277
1
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 349 publications
(309 citation statements)
references
References 24 publications
27
277
1
4
Order By: Relevance
“…This peak is located at an almost constant energy, in an energy region typical of the boson peak (BP), as it will be also shown from the more detailed analysis. The comparison with experimental results on other systems and with moleculardynamics simulations 7,8,23 suggests the interpretation of this low-frequency feature as the high-frequency evolution of the transverse-acoustic mode. 25 However, it should be noted that the density fluctuation modes loose their symmetry as the wave vector is increased, so that the longitudinal and transverse terms have not a well defined significance.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…This peak is located at an almost constant energy, in an energy region typical of the boson peak (BP), as it will be also shown from the more detailed analysis. The comparison with experimental results on other systems and with moleculardynamics simulations 7,8,23 suggests the interpretation of this low-frequency feature as the high-frequency evolution of the transverse-acoustic mode. 25 However, it should be noted that the density fluctuation modes loose their symmetry as the wave vector is increased, so that the longitudinal and transverse terms have not a well defined significance.…”
Section: Methodsmentioning
confidence: 84%
“…As to the behavior of the peak broadening on varying the momentum transfer, a Q 4 dependence below 10 nm −1 is observed 7 for both random-network and molecular glasses, while a Q 2 dependence of the line width is observed in the nm −1 range. 8,9 These trends have been more recently enhanced in glycerol glass 10 observing the transition between Q 4 and Q 2 trends at about 2 nm −1 . The broadening of the peaks and its origin is one of the most debated characteristic of the glassy state and clearly indicates that these collective excitations are originated by a complex set of atomic or molecular motions linked to the intrinsic disorder of the system.…”
Section: Introductionmentioning
confidence: 99%
“…2(b)], the present data, confirming the result of the high temperature study, show a behavior which is not a simple ∝ Q 2 law, as found in the previous experiments. [27][28][29][30] On the contrary, the damping undergoes a transition from ∝ Q 4 in the low-Q range to ∝ Q 2 at high Q's (see Ref. 23 for a thorough discussion on this point).…”
Section: A Dispersion and Dampingmentioning
confidence: 99%
“…3 The observation of these elastic anomalies requires a very high accuracy which has been attained only in recent years, thanks to the continuous development of the IXS technique. The particular case of vitreous silica has been deeply studied by means of IXS in the past, [26][27][28][29][30][31][32][33][34][35] but these fine features of the dynamics were hidden by the noise in the first experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the lack of periodicity in such materials, the presence of phonon-like excitations in glasses has been documented in IXS experiments 16 . These are manifested by the presence of dispersion relations that persist up to wavevectors' magnitudes, Q, which are a significant fraction of the first maximum of the static structure factor, S(Q) 16 .…”
mentioning
confidence: 99%